PENGEMBANGAN SUMBER BELAJAR IPS MELALUI PEMANFAATAN LINGKUNGAN DALAM PENINGKATAN KETERAMPILAN PROSES DI SEKOLAH DASAR - Soraya, Soraya; Amalia, Ice Rezeki; Nafsia, Yuna Salimatun; Nisa, Fitrih Hijratun; Syafruddin, Syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Social studies as one of the subjects in elementary school that aims to prepare the whole Indonesian man who is able to take part in the life of modern society. Social studies also discusses the problems in society included in the relationship between humans and their environment. Social studies learning concepts in elementary school are mostly abstract applied in the teaching and learning process. By involving students as the center of learning activities, the learning process is expected to be quality and the role of the teacher in this learning process is not as an instructor but as a facilitator. This study aims to reveal how the implementation of environment-based social studies learning in this school by conducting a study on the Utilization of the Environment in Social Studies Learning in Elementary Schools. The method used in this research is to use descriptive qualitative method that aims to describe the state or one phenomenon, then the data analysis used to analyze the results of the research is adapted to the existing data. The results showed that the learning process with the utilization of the environment as a source of learning social studies in elementary school has been maximized, students are more motivated to learn because the learning atmosphere becomes more fun, become more real, and provide knowledge in accordance with the cognitive level of elementary school age children. Utilization of the environment as a learning resource can also create students who care about the surrounding environment, because students are in direct contact with the environment where they live. Students' knowledge is not only fixated on the textbook taught by the teacher, but students can experience firsthand the material taught. So that it can make this learning an experience and make meaningful learning (meaningful learning).